Printing Tools to Make Paper Bags Worth For Selling Students with intellectual Disabilities - Kasiyaninggsih, K. (Universitas Pendidikan Indonesia (UPI), 2021)
This study was to determined the effectiveness of using printing equipment to made paper bags suitable for sale for students with intellectual disabilities. This researched was a classroom action researched using the demonstration method. The subject of research was class X which consists of 4 students at special needs school-C Sukapura Bandung. The results showed an increase in the ability of students with intellectual disabilities in making paper bags worth selling, where each student could exceed the specified minimum completeness criteria of 80. This was because the tool could ease the difficulties experienced by students with intellectual disabilities, in terms of neat folding, standard measurements, gluing, and speed, when the paper bags manufacturing processed, is worth selling. With this tool, students with intellectual disabilities would have the skills, so they could live independently after graduation.